meta-PBI/methylated PBI-OO blend membranes for acid doped HT PEMFC - Cho, Hyeongrae; Hur, Eun; Henkensmeier, Dirk; Jeong, Gisu; Cho, Eunae; Kim, Hyoung Juhn; Jang, Jong Hyun; Lee, Kwan Young; Hjuler, Hans Aage; Li, Qingfeng; Jensen, Jens Oluf; Cleemann, Lars Nielausen (Pergamon Press Ltd., 2014)
Methylation of polybenzimidazole leads to positively charged polymer backbones, and moveable anions. Ion exchange of methylated PBI-OO in phosphoric acid (PA) shows that the resulting polymers dissolve. meta-PBI, however, absorbs about 400 wt% PA while remaining a self supported membrane. We investigate the properties of blend membranes, employing meta-PBI for mechanical integrity and methylated PBI-OO for high PA uptake and resulting proton conductivity. While small additions of PBI-OO decrease the tensile strength of blend membranes (58 MPa for 10% PBI-OO), further addition leads to an increase, and 50% blend membranes show again a tensile strength of 74 MPa, just 3 MPa lower than pure meta-PBI membranes. Thermal stability of iodide exchanged blend membranes appears to be remarkably high, probably because cleaved iodomethane does not evaporate but methylates meta-PBI. PA concentration in doped membranes of 60-63% is reached by doping in 60% PA (blend; 6.3 PA/repeat unit) and 70% PA (meta-PBI; 4.6 PA/r.u.). This suggests that blends absorb PA more strongly. Both membranes show similar conductivity between rt and 140 degrees C, indicating that PA concentration describes these membranes better than PA/r.u. In the fuel cell, blend membranes show similar or better performance than meta-PBI. In the TGA, blends doped in 20% PA showed a stable plateau between 115 and 180 degrees C, while meta-PBI lost weight continuously. (C) 2014 Elsevier Ltd. All rights reserved.